PELATIHAN PENYUSUNAN SOAL HIGHER ORDER THINKING SKILLS (HOTS) BAGI GURU SMP DI KECAMATAN TEHORU - Huwaa, Novalin Calasin; Moma, La; Sapulette, Fentje (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service activity aims to train junior high school teachers in Tehoru sub-district to prepare Higher Order Thinking Skills (HOTS) questions. To find out the results of the training carried out, junior high school teachers in the Tehoru sub-district about preparing HOTS questions were given a questionnaire about their knowledge of preparing HOTS questions before and after attending the training. With training in the preparation of HOTS questions, teachers have understood how to prepare HOTS questions correctly. This can be seen from the results of the presentations of teachers in the training and changes in the results of the questionnaire scores before and after attending the training. The number of teachers who were hesitant and unable to prepare HOTS questions before the training was 16 people (88.9%). After attending the training, the number of teachers who have been able to compose HOTS questions is 18 people (100%)